Determination of Polyphenols in Tobaccos by High Performance Liquid Chromatography with Matrix Solid-Phase Dispersion Extraction and Clean-Up - Liang, Fengxia; Zhang, Zhenyu (Asian Journal of Chemistry, 2010)
A simple method for the determination of polyphenols in tobaccos using matrix solid-phase dispersion (MSPD) and high performance liquid chromatography was developed. The dry ground tobaccos and octadecyl bonded silica (C18) adsorbent were ground with a pestle to produce a homogenous material for MSPD column. Eluted with methanol (0.003 mol/L) and aqueous hydrochloric acid (80:20, v:v), the interfering components such as grease and wax were retained in the C18 adsorbent and the extract was clean enough for direct injection into HPLC. The mobile phase of methanol-trifluoroacetic acid (0.03 %) (pH = 2.5) was used for gradient elution. A 345 nm was selected as detection wavelength. The recoveries of tobacco polyphenols were from 94.0 to 97.5 % and the relative standard deviations were in the range of 3.62-6.31 %. The new method was compared with a conventional method based on the use of refluxing extraction followed by solid-phase extraction clean-up. The consumption of less sample preparation time and fewer toxic solvents with better clean-up efficiency than refluxing extraction SPE clean-up technique indicates the suitability of this method.